2016
DOI: 10.1111/1467-8578.12127
|View full text |Cite
|
Sign up to set email alerts
|

Reading assessments for students with ASD: a survey of summative reading assessments used in special educational schools in the UK

Abstract: Schools have an obligation to assess the literacy skills of their students, and the provision of reading instruction to students includes the ability to measure progress in this area. However, the design of reading tests includes the ability not only to read words, but also the ability to verbalise them. This presents a particular challenge for practitioners working with students with autism spectrum disorders (ASD) who can be nonverbal in many cases. How this issue is generally overcome is currently unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Much research in the area of educational assessment has focused on mainstream schools. Although only around 29% of autistic children are educated in special schools (Arnold and Reed 2016), it is important to ensure that school-based assessments are appropriate for these pupils. Aside from the statutory assessment of core curriculum subjects (English, maths and science), there is no specification of how other areas of learning are assessed, leaving the format of assessment to individual schools (Office for Standards in Education 2019).…”
Section: Assessment In Special Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Much research in the area of educational assessment has focused on mainstream schools. Although only around 29% of autistic children are educated in special schools (Arnold and Reed 2016), it is important to ensure that school-based assessments are appropriate for these pupils. Aside from the statutory assessment of core curriculum subjects (English, maths and science), there is no specification of how other areas of learning are assessed, leaving the format of assessment to individual schools (Office for Standards in Education 2019).…”
Section: Assessment In Special Educationmentioning
confidence: 99%
“…Coexisting intellectual disabilities are also associated with an increase in challenging behaviour and difficulties with social skills (Walton and Ingersoll 2013). Around 25% of this population are pre-or minimally verbal (Arnold and Reed 2016) and the possible requirement for special education provision is one of the reasons autistic individuals with intellectual disabilities are considered a group with distinct needs compared with those with autism alone (Matson and Shoemaker 2009).…”
mentioning
confidence: 99%
“…Keďže na trhu nie je žiadna skúška čítania, ktorá by bola vytvorená pre žiakov s mentálnym postihnutím, rozhodli sme sa pre skúšku čítania práve od Mikulajovej a Váryovej. Na problém diagnostiky čítacích zručností žiakov so špeciálnymi edukačnými potrebami (najmä u nehovoriacich žiakov) upozorňujú vo svojom výskume autori Arnold a Reed (2016). Skúška čítania od Mikulajovej a Váryovej nám umožňuje analyzovať a hodnotiť techniku čítania, porozumenie čítanému textu, pochopenie významu čítaného textu a chyby pri čítaní -viac informácií o teste si čitateľ nájde v publikácii (Mikulajová a kol., 2012).…”
Section: Výskumné Metódyunclassified
“…With regard to methods of assessing reading used for nonverbal pupils with ASD, Arnold and Reed () investigated tests employed in additional learning needs (ALN) settings. The results of the survey indicated that the most popular formats for reading assessment were those that carry a requirement to verbalise the sentences being read.…”
mentioning
confidence: 99%
“…In terms of what we aimed to measure in the current study, we shall borrow the phrase ‘context free word recognition’ from Gough and Tunmer (). The New Salford Reading Test (NSRT) was identified as the most popular test being used in ALN schools in Arnold and Reed’s () study and therefore, this was the test we chose to deliver. While a comprehension test accompanies the NSRT, it is important to note that only the test which measures word recognition ability was delivered.…”
mentioning
confidence: 99%